Environmental motivation or economic motivation? Explaining individuals’ intention to carry reusable bags for shopping in China - Li, Yong; Wang, Bairong (Frontiers in Psychology, 2022)
To achieve satisfying effects of plastic ban policies, it is important to promote people’s green bag using intention. Many studies have examined the antecedents of reducing plastic bag usage, but research regarding the influential factors of reusable bag usage is limited. Based on a survey data of 532 respondents in China, a multiple linear regression model is constructed in this study to examine the determinants of individuals’ reusable bag using intention. Results show that plastic ban awareness, social responsibility, environmental motivation and economic motivation significantly and positively affect individuals’ reusable bag using intention. Of the two motivation factors, environmental motivation impacts more. More importantly, economic motivation positively moderates the relationship between environmental motivation and reusable bag using intention. This finding suggests a motivation “crowding in” effect in predicting people’s intention to carry reusable bags for shopping. Results of this study also indicate that female, older, and richer people are more inclined to carry reusable bags for shopping. Implications for plastic crisis management are discussed.